Environmental Drivers of Habitat Use by Hawksbill Turtles (Eretmochelys imbricata) in the Arabian Gulf (Qatar) - Marshall, Christopher D.; Cullen, Joshua A.; Al-Ansi, Mehsin; Hamza, Shafeeq; Abdel-Moati, Mohamed A. R. (Frontiers in Marine Science, 2020)
Climate change challenges life across all ecosystems. A majority of the increased thermal energy expected from climate change will be absorbed by the oceans, increasing sea surface temperature of the world’s oceans. Although, the impacts of climate change is more well-known for terrestrial ecosystems, there is growing evidence that climate change results in shifts in the range, abundance and phenology of marine species. Marine turtles are an interesting model system to investigate the impacts of climate change. As secondarily aquatic tetrapods they face numerous challenges in both terrestrial and marine habitats. Marine turtles in the hottest marine system in the world, the Arabian (Persian) Gulf, provide an unusual opportunity to investigate how climate change impacts the natural history of these ectotherms. The Arabian Gulf has become known as a living laboratory for climate change since SSTs can range up to 35°C, near the thermal physiological tolerance of most marine organisms. Bayesian switching state-space models of hawksbill turtle movement derived from satellite tags demonstrate that individuals seasonally moved to a 40-50 m isobath deep-water thermal refugia in the southeast Arabian Gulf seasonally when SST increased > 32°C. Generalized Additive Mixed Models demonstrate that SST was the primary driver of turtle movement, but depth (Z), sea surface height anomaly (SSHa) were also important factors. Furthermore, bathymetric rugosity was an important habitat characteristic for deep-water habitats. Climate models show that air, and therefore ocean, temperatures will continue to increase over time. It is likely that this migration to deep water habitats, and time spent there, will lengthen. Marine turtles in this part of the Gulf may sacrifice foraging opportunities to use thermal refugia, which may have serious consequences for hawksbill population sustainability in the region and points to long-term population sustainability issues globally for this endangered species.